Hypertension, a dementia polygenic risk score, APOE genotype and incident dementia - Littlejohns, T; Collister, J; Liu, X; Clifton, L; Tapela, N; Hunter, D (Wiley, 2022)
Introduction There is inconsistent evidence on whether genetic risk for dementia modifies the association between hypertension and dementia.